Social marketing to the business customer : listen to your B2B market, generate major account leads, and build client relationships - Gillin, Paul (Wiley, 2011)
The first book devoted entirely to B2B social marketing B2B markets are fundamentally different from consumer markets. Decisions are made on value, not impulse. Buying cycles are complex, often with many stakeholders involved. Relationships and support are critical. Bet-the-business decisions demand discipline, knowledge, and lots of information. This hands-on guide covers topics unique to this segment, including cost justification, prospecting and lead generation, matching tools to the sales funnel, building, B2B search engine optimization, social media monitoring, social media policy development, long-term client relationships, gaining stakeholder support, building a more transparent organization, and what's coming next. Features plentiful examples, case studies, and best practices Focuses on the channels that are most effective for B2B marketers Builds on the authors' more than 30 years of combined experience in the new media/social media space, as well as two previous successful books Leverage the vast business-to-business potential of Facebook, LinkedIn, Twitter, and many other social media platforms today with Social Marketing to the Business Customer!